ROTATIONALLY SYMMETRIC TRANSLATORS OF THE GAUSS CURVATURE FLOW - Aydin, Muhittin Evren; López, Rafael (Technical University of Civil Engineering of Bucharest, 2023)
We completely classify in Euclidean 3?space the rotational translators of the flow by powers of the Gauss curvature. This classification is also extended to Lorentz-Minkowski 3?space. © 2023, Technical University of Civil Engineering of Bucharest. All rights reserved.
Keywords: Euclidean space; K?-translator; Minkowski space; rotational surface